Analysis of the gyroscopic effect on the hydro-turbine generator unit. (1st October 2019) - Li, Jianling; Chen, Diyi; Liu, Gongcheng; Gao, Xiang; Miao, Kebin; Li, Yingxi; Xu, Beibei
Highlights: A multi-degree-of-freedom nonlinear dynamics model with the gyroscopic effect is proposed for the Hydro-turbine generator unit (HTGU). The influence of the gyroscopic effect on the vibration characteristics of the high-speed rotating HTGU shafting system has been studied. The influence of the gyroscopic effect on the vibration characteristics of the generator rotor and the turbine runner are compared and analyzed by setting blank group respectively. Abstract: The existence of the gyroscopic effect has significant impact on the stability, dynamical behaviors and vibrational characteristics of the high-speed rotating systems. In this paper, the vibration characteristics of the hydro-turbine generator unit with the gyroscopic effect is analyzed. First, a novel nonlinear mathematical model of the hydro-turbine generator unit with consideration of the gyroscopic effect and multi-degree of freedom is established. Second, the vibration of the shaft system are investigated using time histories, phase trajectories and spectrograms based on an operation hydropower station. Some interesting phenomena are obtained by comparing the vibration laws of the hydraulic generator unit in the cases of both K  = 0 (without gyroscopic effect) and K  ≠ 0 (with gyroscopic effect). Those phenomena show that the effect of gyroscopic intensifies the vibration to some components of the hydraulic generator unit, and it has significant effect on the safe and stable operation of hydropower stations. Meanwhile, the proposed mathematical model can accurately reflect the influence of gyroscopic effect on the vibration characteristics of the hydro-turbine generator unit. The results of this study provides theoretical basis for the design and installation of hydraulic generator units and the optimal operation of hydropower stations.